Unveiling Liquation and Segregation Induced Failure Mechanism in Thick Dissimilar Aluminum Alloy Electron-Beam Welds - P. Mastanaiah; G. Madhusudan Reddy; Anirban Bhattacharya; Angshuman Kapil; Abhay Sharma (Metals, 2022)
This study presents new findings on the underlying failure mechanism of thick dissimilar electron-beam (EB) welds through a study on the AA 2219-AA 5083 pair. Contrary to the prior studies on EB welding of thin Al alloys, where liquation in the grain boundaries (GBs) in the partially melted zone (PMZ) was not observed, the present investigation for thick EB welds reports both liquation and increased segregation of Cu in the PMZ. The work is thus directed towards understanding the unusual observation in the PMZ of thick EB weld through investigation of the microstructural variation across the various regions of the produced weld. The microstructural results are correlated with the mechanical properties of the weld, i.e., hardness variation and tensile response. Results of this investigation suggest that unlike the convention that EB welding produces sound dissimilar Al welds, the weld performance for thick EB Al welds is affected by the heat input, the associated cooling rates, and most importantly by the base material thickness. Extensive liquation and Cu segregation induced failure in the PMZ on the AA 2219 side of the dissimilar weld. The underlying failure mechanism is explained through a heat-transfer analysis. Beyond a certain plate thickness, the heat transfer changes from two to three-dimensional. As a result, retarded cooling promotes liquation and Cu segregation in thick EB welds.